Building a regional health agenda: A rights-based approach to health in South America. Issue 9 (2nd September 2018) - Herrero, María Belén; Loza, Jorgelina
ABSTRACT: Attention to health policies in Southern regional organisations reveals a new 'social turn' in the regional political economy of international cooperation. The aims of this paper are twofold. First, it aims to establish the extent to which the Union of South American Nations (UNASUR) has adopted and sustained policy interventions committed to addressing social inequities and asymmetries in relation to health, as indicated by regional policy agendas, policy development processes and resourcing. Second, it seeks to understand how UNASUR is mobilising national and regional actors in support of such policies. Our analysis of documentary sources and interviews leads us to draw the following conclusions. First, we argue that the UNASUR regional framework has a committed social equity/rights focus in relation to access to health care and medicines, with a clear focus on reducing asymmetries between countries. Second, although UNASUR does not enforce national commitments on health and medicines, it nonetheless plays a role in expanding domestic policy horizons and policy capacities. In this respect, we find that UNASUR interventions lead to initiatives and actions aimed at implementing reforms, setting targets and defining goals nationally. Third, in global arena, UNASUR enhances the visibility and 'voices' of the member states.